Risk factors for paediatric cancer in the Gaza Strip: a case-control study. (21st February 2018) - Elnuweiry, Heiam A; Abed, Yehia
Abstract: Background: Cancer is a serious health problem and the third leading cause of death in the occupied Palestinian territory, both in adults and children. For most children younger than 18 years who have cancer, there is no obvious cause. The aim of this study was to identify the main risk factors for paediatric cancer in the Gaza Strip. Methods: This case-control study was done in five Gaza Strip governorates. We enrolled children diagnosed with paediatric cancer and receiving treatment at oncology departments at Ranteesy Specialised Paediatric Hospital, Al Shifa Hospital, and at the European Gaza Hospital in 2012 and 2013. Controls were children who visited primary health-care centres and matched for locality, age, and sex. We used face-to-face questionnaires to interview the children's parents and χ 2 tests for analyses. Findings: 292 children were enrolled in this study. 146 children had been diagnosed with paediatric cancer (70 [48%] children had a solid tumour, 50 [35%] had haematological cancer, and 25 [17%] had a lymphoma tumour). 146 children were enrolled as controls. The main risk factors associated cancer were exposure to ultrasound during gestational period (p<0·0001) and family cancer history (p=0·001). For environmental factors, we found associations of paediatric cancer with family history of smoking (p=0·016), exposure in pregnancy to passive smoking (p=0·018), and white phosphorus (p<0·0001). Agriculture pesticides and herbicides were not associated with paediatric cancer. Furthermore, the parents' educational level and occupation and the mother's exposure to x-rays were not associated with paediatric cancer. Interpretation: The study presents data on several potentially avoidable environmental risk factors for paediatric cancer in the Gaza Strip. Funding: None.